Influence of Company Characteristics on Corporate Social Responsibility Disclosures in the Annual Reports of the Manufacturing Companies - Ramadhani, Chintiya Febiana; Agustina, Linda (Accounting Analysis Journal, 2019)
This study aims to analyze the influence empirically about the characteristics of the company towards disclosure of CSR (Corporate Social Responsibility). All manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2014 to 2016, namely 149 companies were the population used to determine whether or not there was influence between the characteristics of companies and disclosure of CSR. The sample in this study was taken using purposive sampling technique and selected a sample of 83 companies with 249 units of analysis and observation period for 3 years. Multiple regression analysis using IBM SPSS 24 is a data analysis technique used as a hypothesis testing tool. The results of this study prove that the first hypothesis, namely profitability can affect CSR disclosure, CSR disclosure is also influenced by how large the size of a company, and the leverage variable also has an influence on CSR disclosure but the direction is negative. While other variables, namely the size of the board of commissioners and public share ownership have no effect on CSR disclosure. The conclusion of this study is that the higher the level of profitability and size of the company can influence the increase in information about CSR disclosure, while the increase in the value of leverage makes the company will reduce information about the disclosure of CSR.